Deep brain stimulation of thalamus for epilepsy - Robert S. Fisher (Neurobiology of Disease, 2023)
Neuromodulation (neurostimulation) is a relatively new and rapidly growing treatment for refractory epilepsy. Three varieties are approved in the US: vagus nerve stimulation (VNS), deep brain stimulation (DBS) and responsive neurostimulation (RNS). This article reviews thalamic DBS for epilepsy. Among many thalamic sub-nuclei, DBS for epilepsy has been targeted to the anterior nucleus (ANT), centromedian nucleus (CM), dorsomedial nucleus (DM) and pulvinar (PULV). Only ANT is FDA-approved, based upon a controlled clinical trial. Bilateral stimulation of ANT reduced seizures by 40.5% at three months in the controlled phase (p = .038) and 75% by 5 years in the uncontrolled phase. Side effects related to paresthesias, acute hemorrhage, infection, occasional increased seizures, and usually transient effects on mood and memory. Efficacy was best documented for focal onset seizures in temporal or frontal lobe. CM stimulation may be useful for generalized or multifocal seizures and PULV for posterior limbic seizures. Mechanisms of DBS for epilepsy are largely unknown, but animal work points to changes in receptors, channels, neurotransmitters, synapses, network connectivity and neurogenesis. Personalization of therapies, in terms of connectivity of the seizure onset zone to the thalamic sub- nucleus and individual characteristics of the seizures, might lead to improved efficacy. Many questions remain about DBS, including the best candidates for different types of neuromodulation, the best targets, the best stimulation parameters, how to minimize side effects and how to deliver current noninvasively. Despite the questions, neuromodulation provides useful new opportunities to treat people with refractory seizures not responding to medicines and not amenable to resective surgery.